Prioritizing Maintenance Strategies for Efficient Forklift Performance Through Failure Analysis: Memprioritaskan Strategi Perawatan untuk Kinerja Forklift yang Efisien Melalui Analisis Kegagalan - Rizky, Naufal; Sulistiyowati, Wiwik (Indonesian Journal of Innovation Studies, 2024)
This study addresses forklift maintenance challenges at PT. Karya Mitra Teknik, focusing on undisciplined operators and overuse issues. Using Failure Mode And Effect Analysis (FMEA) and Fault Tree Analysis (FTA), it identifies root causes and suggests improvements. Data collected through observations, interviews, and flow diagrams pinpoint three priority failure modes: radiator, starter dynamo, and oil flow failure. Recommendations emphasize regular maintenance, cleanliness, and enhanced operational practices for effective issue mitigation. Highlight: Root Cause Analysis with FMEA and FTA. Prioritizing Critical Failure Modes. Recommend Disciplined Maintenance for Operational Enhancements. Keyword: Forklift Maintenance, Root Cause Analysis, Improvement Recommendations, FMEA, FTA